Turismo en el cantón Sigchos, provincia de Cotopaxi. Marketing estratégico para su posicionamiento. - Velásquez Beltrán, Alex Javier (2020)
The present project, titled "Tourism in Sigchos Canton, Cotopaxi Province. Strategic Marketing for its positioning" proposes a group of marketing strategies oriented to the positioning of the canton as one of the main tourist destinations, within the province of Cotopaxi, at a national and international level. For many time the competent organizations, in tourist topic, have let ignore all the tourist potential that our country and some regions in specific have, as it is the case of the Sigchos canton. Tourism represents, for the economy in general, an important source of resources both for the locality and for the people who are directly or indirectly involved in this activity. The Decentralized Autonomous Government of the Sigchos Canton, through its competent management of the individual, seeks to generate the ideal space for the promotion of tourism. The process begins by discovering and analyzing the tourism potential that the Sigchos Canton can offer, in terms of destinations and service offerings; The process begins by discovering and analyzing the tourist potential that Sigchos County has to offer in terms of destinations and services. The strategies are based on a field research that included the application of an observation card that was used to prepare an inventory of 11 tourist attractions visited and a survey of the floating population in the town, which showed the real reality of tourism in the town, Therefore, it can be concluded that the Sigchos canton has the ideal conditions for accommodation, food, infrastructure, access, recreation and basic services to integrate into the local, national and international system of tourism services offered by Ecuador, making it one of the most important historical and cultural icons of the province of Cotopaxi